Local Governance in Developing Countries - Shah, Anwar (Washington, DC: World Bank, 2012)
This book develops a comparative institutional framework for responsive, responsible, and accountable governance in developing countries. It provides a synthesis of analytical literature on local governance. It traces the historical evolution of local governance and presents a stylized view of alternative models of local governance practiced in various countries. It also presents case studies for 10 countries by leading national and international scholars. The country case studies present an in-depth view of local government organization and finance in each country.